Usage of Low-Pressure Water Sources and Hydroturbines Working in Them (Texas Journal of Engineering and Technology, 2023)
The article examines the state of electricity production and the use of hydropower sources in the Republic of Uzbekistan, and the effectiveness of the Jonval-Genshel hydro turbine of the micro hydroelectric power plant designed to use the existing low-pressure water sources in the republic.